(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
This research concentrates on characterizing the sandstone reservoir features within the Bhuban Formation exposed in the Sitakund Anticline of the Chittagong Hill Tracts. Of the lack of well-qualified reservoirs, the sandstone facies in the Bhuban Formation are considered the primary reservoir source and a significant contributor to Bangladesh’s hydrocarbon reserves. The Bhuban Formation showcases a pattern of alternating sandstone and shale layers. To ascertain the existence of reservoir sandstone facies in the Bhuban Formation, the study conducts analyses of exposed structures along various outcrop sections of Bariyadhala, Chandranath, Barabkunda, and Shahasradhara. Through scrutinizing lithology, sedimentary structures, bed configuration, grain size, and reservoir characteristics of rock sequences, three distinct facies types emerge: the alternating sandstone and shale layers, channel sand, and incised valley sand. These facies types signify diverse depositional environments, with the alternating sandstone and shale layers originating from tidal flats, channel sand representing sediment fill within tidal channels, and incised valley sand indicating sediment accumulation within incised valleys. The detailed petrographic analysis underscores that the incised valley fill sand exhibits the most favorable reservoir qualities, boasting an approximate porosity of 25%. The tidal channel fill and the tidal flat deposits display 20% and 8% porosity, respectively. Both channel sand and incised valley sand showcase commendable porosity and permeability. In contrast, the sample featuring the alternation of sandstone and shale has the lowest porosity and contains randomly oriented clay minerals, predominantly Kaolinite. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 12(1), 2023, P 57-68